(untitled) (Historia, 2021)
In a 1795 publication, the last before his untimely death, the French philosopher A-N. Condorcet noted : (P)hilosophy and the sciences are necessarily neglected in all countries where there is an honourable occupation leading to wealth and position that is open to anyone who has a natural inclination for study.